Potential role of a nutraceutical spice (Allium hirtifolium) in reduction of atherosclerotic plaques - Rafieian-kopaei Mahmoud; Keshvari Mahtab; Asgary Sedigheh; Salimi Maryam; Heidarian Esfandiar (Shahrekord University of Medical Sciences, 2013)
Introduction: Spices are now considered as agents that not only can prevent but may even treat chronic diseases. This study was aimed to investigate the effects of Allium hirtifolium as a hypolipidemic and anti-atherosclerotic substance in hypercholesterolemic rabbits. Methods: Twenty four adult New Zealand male rabbits were divided randomly into 3 groups of 8 animals each and treated for 60 days as follows. Normal group received basal feed, while the two intervention groups were fed with hypercholesterolemic diet (1% cholesterol) and hypercholesterolemic diet plus A. hirtifolium extract, respectively. At the start and the end of the experiment, fasting blood was taken from all animals. Serum concentrations of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), apolipoproteins A and B, serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), high-sensitivity C-reactive protein (hs-CRP), glucose and insulin were measured at the end of supplementation period in all studied groups. Atherosclerotic plaque thickness of aorta to media was also determined in all groups. Results: Rabbits fed only with high cholesterol diet showed increased atherosclerotic plaque thickness to media compared to the control group, while the group fed with hypercholesterolemia diet plus A. hirtifolium extract significantly decreased atherosclerotic plaque thickness to media, TC, TG, LDL-C, and significantly increased HDL-C compared to hypercholesterolemic diet group. Supplementation with A. hirtifolium extract did not cause any significant alteration in apolipoproteins, SGOT, SGPT, hs-CRP, glucose and insulin compared to the hypercholesterolemic diet group (p>0.05). Conclusion: Ethanolic extract of A. hirtifolium ameliorates fatty lesions in aorta and may reduce risk factors of cardiovascular diseases.